Thrombotic risk factors for cardiovascular disease - Lowe, Gordon (Henry Stewart Talks, 2008)
Thrombosis: arterial and venous, Processes in thrombosis, Platelets, Coagulation, Coagulation factors, Coagulation Inhibitors, Coagulation activation markers, Fibrinolysis